Bioconvection transport of magnetized Walter's B nanofluid across a cylindrical disk with nonlinear radiative heat transfer. (August 2021) - Waqas, Hassan; Alghamdi, Metib; Muhammad, Taseer; Khan, Muhammad Altaf
Abstract: Nanotechnology plays a crucial role in the main innovation development of the modern age in the latest technology. In recent times, researchers are concentrated to build up various algorithms to increase their heat transfer rate. One of the approaches that have conquered this deficiency is to significantly raise the thermal properties of regular fluids by manifestation of nanoparticles in host fluids. In this article, a numerical study is developed to investigate the bio convective transport of Walter's B nanofluid past a cylindrical disk in the presence of thermophoretic and Brownian diffusions. Additionally, non-linear thermal radiation, variable thermal conductivity and motile microorganisms are also considered. The Buongiorno model is used to explore the nanofluid features with motile microorganisms. The constituted normalized system of modeled flow equations is condensed into dimensionless system of differential form by adopting appropriate similarity variables. The ordinary systems are elucidated through bvp4c technique in MATLAB software. Characteristics of flow parameters against velocity field, temperature distribution, volumetric concentration of species and microorganism's profile are discussed. From the results we observed that velocity field is reduced for larger magnetic parameter. It is noticed that developing values of mixed convection parameter raises the velocity field. It is analyzed that temperature distribution of Walter's B fluid upsurge for variable thermal conductivity parameter. Temperature field intensifies for thermal Biot number. It is perceived that solutal field of species diminishes for larger Brownian motion parameter. The microorganism field is found to decay with Peclet and bioconvective Lewis numbers. The current proposed model is more useful in the field of engineering. The improvement in heat transfer rate is current issue in the world. Nanofluids have high thermal efficiency therefore such fluids are more useful to improve the heat transfer rate.